MENILAI PROPERTI PSIKOMETRI LIFE-SPACE ASSESSMENT (LSA) DALAM MENGUKUR LIFE-SPACE MOBILITY (LSM) PADA PASIEN PASCA STROKE - Ni Komang Triya Darma Cahyani; Govinda Vittala; Sayu Aryantari Putri Thanaya (Indonesian Journal of Physiotherapy, 2026)
Background: Life-Space Mobility (LSM) is a concept that assesses a person's mobility based on the range of movement and participation in daily activities. Meanwhile, the Life-Space Assessment (LSA) is one of the LSM measurement tools that was initially developed for the elderly population and is now being applied to post-stroke patients. However, a more in-depth review is still necessary regarding the psychometric properties of LSA in post-stroke patients. Objective: This literature review aims to evaluate the psychometric properties of LSA in post-stroke patients and review its potential application in Indonesia. Methods: A literature search was conducted on the PubMed database, and Google Scholar with keywords related to LSM, LSA, stroke, and psychometric properties. Studies that met the inclusion criteria were then evaluated using the psychometric property quality criteria from Terwee et al. (2007). Results: Of the 822 articles found, five studies were selected based on the inclusion and exclusion criteria. LSA showed good content validity, with adequate internal consistency (Cronbach's alpha 0.73–0.85). Construct validity varied, with several studies showing weak correlations with other measuring instruments. Reliability is generally high (ICC > 0.70), while responsiveness and floor/ceiling effects still require further research. Conclusion: LSA is a potential measurement tool to assess LSM in post-stroke patients. However, further research is needed regarding its validity and responsiveness, especially in the context of the Indonesian language and culture, to ensure its accurate and relevant application.